A Conservative treatment approach in the management of radicular cyst associated with primary mandibular molars: A case report - Ghadge, Sanjana; Pradhan, Debapriya; Katge, Farhin; Jain, Khushboo; Krishna, Vamsi (Journal of Orofacial Research, 2019)
Radicular cysts are the most common cystic lesions occurring in the jaws arising from the inflammatory activation of cell rests of malassez. They may arise from infected primary molars. Radiographically they appear either as unilocular or multilocular radiolucency delineated by a radiopaque border. Treatment includes extraction of the tooth or endodontic therapy of necrotic pulp followed by enucleation of the cyst. Here we report a case of a nine year old boy who visited the outpatient department with a chief complaint of swelling and pain in lower right region of jaw. On the basis of history, clinical examination and radiographic investigations, a diagnosis of radicular cyst was made. In our case a conservative treatment approach of only extraction was considered keeping in mind that, in children there is a high propensity for healing and formation of bone.